2012
DOI: 10.1186/2192-1709-1-4
|View full text |Cite
|
Sign up to set email alerts
|

Landscape features and weather influence nest survival of a ground-nesting bird of conservation concern, the greater sage-grouse, in human-altered environments

Abstract: Introduction: Ground-nesting birds experience high levels of nest predation. However, birds can make selection decisions related to nest site location and characteristics that may result in physical, visual, and olfactory impediments to predators. Methods: We studied daily survival rate [DSR] of greater sage-grouse (Centrocercus urophasianus) from 2008 to 2010 in an area in Wyoming experiencing large-scale alterations to the landscape. We used generalized linear mixed models to model fixed and random effects, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 52 publications
8
63
1
Order By: Relevance
“…Biotic and abiotic processes operate and interact at multiple spatial scales on the landscape (Turner 1989), which suggests that no single spatial scale likely exists for multiple landscape metrics that may influence avian nest success and/or survival (Stephens et al 2005, Webb et al 2012. Therefore, we evaluated non-random turkey nest site selection at multiple spatial scales (15-[nest site], 40-, 80-, 120-, 160-, and 200-m radii) by comparing used (actual nest sites) to available locations (potential nest sites).…”
Section: Habitat Characteristics Across Scalesmentioning
confidence: 99%
“…Biotic and abiotic processes operate and interact at multiple spatial scales on the landscape (Turner 1989), which suggests that no single spatial scale likely exists for multiple landscape metrics that may influence avian nest success and/or survival (Stephens et al 2005, Webb et al 2012. Therefore, we evaluated non-random turkey nest site selection at multiple spatial scales (15-[nest site], 40-, 80-, 120-, 160-, and 200-m radii) by comparing used (actual nest sites) to available locations (potential nest sites).…”
Section: Habitat Characteristics Across Scalesmentioning
confidence: 99%
“…Although other factors, such as food availability (Newton 1991), thermoregulation (Yanes et al 1996), or environmental predictability (Conover et al 2010), may constrain nest-site selection as the primary cause of nest failure, nest predation has long been considered the main factor driving nest-site selection in birds (Lack 1968, Martin 1993, Ibáñez-Álamo et al 2015. Where incubating adults are also themselves at particular risk of predation, avoidance of habitat features that impede vision may also be important in determining nest site, as seen in groundnesting birds breeding in open habitats (e.g., Magaña et al 2010, Webb et al 2012. Because the needs for concealment and a clear view for visual security (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing impacts of NG wells was a mitigation target because research has demonstrated that energy wells can have negative effects on nest productivity (Dzialak et al 2011, Webb et al 2012, Kirol et al in press). We obtained data about active, plugged, and abandoned wells from the Wyoming Oil and Gas Conservation Commission that included location, status date, and spud date (initiation of drilling) updated to December 2011 (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Further, we hypothesized that reservoirs were facilitating the spread of novel predators into sagebrush habitats; such as the striped skunk ( Mephitis mephitis ) and common raccoon ( Procyon lotor ) that are generally associated with water and riparian areas (Larivière and Messier 1998, Armstrong 2008). Finally, reductions in road and well pad construction and reducing disturbance in dense sagebrush stands was expected to diminish direct loss of sage-grouse habitat (Holloran 2005, Doherty 2008) and, increase nest survival because sagebrush cover is associated with nest survival (Webb et al 2012). …”
Section: Introductionmentioning
confidence: 99%